Daily light integral and/or photoperiod during the young plant and finishing stages influence floral initiation and quality of witchgrass and marigold cut flowers - Spall, Caleb E.; Lopez, Roberto G. (Frontiers in Plant Science, 2022)
To produce consistent and high-quality specialty cut flowers throughout the year, growers in temperate climates must utilize controlled environment greenhouses. Research-based information on photoperiod management and supplemental lighting for specialty cut flowers is limiting. Therefore, our objectives were (1) to determine the effect of photoperiod during the young-plant and finishing stages on floral initiation and morphology of witchgrass ‘Frosted Explosion’ (Panicum capillare) and marigold ‘Xochi’ (Tagetes erecta) and (2) to quantify the effect of daily light integral (DLI) on floral initiation and morphology of witchgrass during the finishing stage. Seeds of marigold and multi-seed pellets of witchgrass were sown and placed under 9-, 11- (marigold only), 12-, 13-, 14-, 15-, 16-, 18-, or 24-h photoperiods or a 9-h short day with a 4-h night interruption (NI) from 2200 to 0200 h. Plugs were distributed among 10-, 11-, 12-, 13-, 14-, 15-, or 16-h photoperiods or a 4-h NI, for finishing. Witchgrass was finished under a very low or moderate DLI of ≈3 or 10 mol⋅m–2⋅d–1, respectively, while marigold was finished under a DLI of ≈10 mol⋅m–2⋅d–1. Marigold grown under a photoperiod ≥ 11 h or a 4-h NI during the young-plant stage and finished under an 11- or 12-h photoperiod had thick stems and consistently met the marketable stem length of ≥ 65 cm. Up to 29% and 107% more stems were harvestable under 11- and 12-h finishing photoperiods, respectively, compared to a 10-h finishing photoperiod. Marigold visible buds were delayed, and stems were not harvestable under photoperiods ≥ 13 h or a 4-h NI after 8 weeks. Young witchgrass plants grown under a photoperiod between 14- and 24-h or a 4-h NI and finished under photoperiods ≥ 14 h or a 4-h NI, and at least a moderate DLI, were reliably harvestable (≥ 50 cm long with a fully developed panicle). Witchgrass finished under day lengths < 13 h (rep. 1) or < 14 h (rep. 2) flowered prematurely and were roughly one-sixth the length of harvestable stems at an open flower. All witchgrass stems grown under a very low DLI were shorter and thinner than those grown under a moderate DLI, and none were harvestable. Therefore, we recommend growing marigold ‘Xochi’ young plants under a photoperiod ≥ 11 h or a 4-h NI and finishing under a 12-h photoperiod. Additionally, witchgrass ‘Frosted Explosion’ young plants should be grown under a photoperiod ≥ 14 h or a 4-h NI and finished under photoperiods ≥ 14 h or a 4-h NI to prevent premature flowering. Witchgrass and marigold cut flowers should be finished under a DLI of ≥ 10 mol⋅m–2⋅d–1 for consistent production of high-quality stems.